1968
DOI: 10.1017/s0022172400041267
|View full text |Cite
|
Sign up to set email alerts
|

Survival of wound pathogens under different environmental conditions

Abstract: Moisture is known to favour the survival of Gram-negative bacilli in the environment, while dry conditions favour the survival of Gram-positive cocci (Hellat, 1948; Bardsley, 1948; Lidwell & Lowbury, 1950). Lowbury & Fox (1953) found that the proportion of bacteria which died when their suspending medium evaporated to dryness was much greater with a suspension of Pseudomonas aeruginosa than with one of Staphylococcus aureus or Streptococcus pyogenes; the death-rate of the Gram-negative bacilli which had surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
1

Year Published

1969
1969
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 9 publications
5
11
1
Order By: Relevance
“…From four tested cultures, P. aeruginosa appeared to be the most sensitive to desiccation, which is consistent with previously published data (Skaliy and Eagon 1972;Pettit and Lowbury 1968;Favero 2004). We observed no reliable variance in each microorganism's recovery from different materials and no significant difference in recovery of microorganisms (with the exception of B. subtilis) inoculated on the same material.…”
Section: Figure 51 Recovery Of Air-dried Microorganisms From Differsupporting
confidence: 92%
See 2 more Smart Citations
“…From four tested cultures, P. aeruginosa appeared to be the most sensitive to desiccation, which is consistent with previously published data (Skaliy and Eagon 1972;Pettit and Lowbury 1968;Favero 2004). We observed no reliable variance in each microorganism's recovery from different materials and no significant difference in recovery of microorganisms (with the exception of B. subtilis) inoculated on the same material.…”
Section: Figure 51 Recovery Of Air-dried Microorganisms From Differsupporting
confidence: 92%
“…The number of microorganisms that can be recovered depends on the type of microorganism (i.e., the microorganisms' resistance to air drying), environmental conditions, and the specifics of material to which is the microorganism is applied, among other factors (Pettit and Lowbury 1968;Otter and French 2009) The materials provided by MAMC for the PAEROSOL efficacy evaluation varied significantly. Non-porous floor tile with no pattern and lightly patterned non-porous countertop laminate were materials that were easy to cut, but their surface was hard to moisten uniformly with the microorganism suspension.…”
Section: Efficacy Of Microorganisms' Recovery From Contaminated Matermentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown previously that Gram-positive organisms survive longer than Gram-negative on drying (Pettit & Lowbury, 1968), but little is known of the comparative ability of Gram-negative organisms to survive drying. The isolation of gentamicin-resistant klebsiellae from dry surfaces agrees with the report by Cook et al (1979) who found klebsiellae on 12 of 129 dry surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Our frequent changing and autoclaving of connector-tubing prevents multiplication of Gram-negative bacilli, since moisture does not accumulate and dry conditions are unfavourable to these bacteria (Lowbury & Fox, 1953;Pettit & Lowbury, 1968). There is then insufficient accumulation of bacteria in the tubing to make contamination of the ventilator likely.…”
Section: Discussionmentioning
confidence: 99%